STATUS ANEMIA IBU SAAT HAMIL TERHADAP KEJADIAN STUNTING PADA BALITA USIA 12-23 BULAN DI WILAYAH KERJA PUSKESMAS LIMAPULUH KOTA PEKANBARU - Yulnefia Yulnefia; Andi Ummah Nuswiyah; Syamsul Bahri Riva'i (LPPM Universitas Abdurrab, 2023)
Stunting is defined as the condition of children’s height which is not suitable with their age. The result of their body height measurement index compared to the age (PB/U) less than -2 SD. Based on Indonesian Toddler Nutrition Status Survey data in 2022, the stunting prevalence Riau Province was 17,0%. Limapuluh Sub District is a sub district with the highest number of stunting occurrence in Pekanbaru City with prevalence 4,47%. One of causative factors for stunting is anemia history in the pregnant women. Anemia in pregnant women generally is caused by the physiological change during the pregnancy. When the infant and the baby were born, iron deficiency anemia caused the infant growth inhibited and premature birth until it can cause stunting. If stunting does not get the right management, then it will cause short term and long term impact on the children. To find out the correlation between anemia history in pregnancy and stunting occurrence in toddlers age 12- 23 months in the work area of Limapuluh Community Health Center Pekanbaru City. Used analytic observational study design with cross sectional design. The sampling technique was proportionate stratified random sampling sampling with sample size 142 respondents..The data were tested statistically using Spearman correlation test. There is correlation between anemia history during pregnancy in stunting occurrence p-value 0,000. The value of correlation coefficient was 0,590 which meant the correlation strength was medium. Anemia history during pregnancy are related to stunting occurrence on toddlers age 12-23 months in the work area of Limapuluh Community Health Center Pekanbaru City.